2007
DOI: 10.2981/0909-6396(2007)13[11:fafdii]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Flushing Distance in Incubating Female Greylag Geese Anser Anser

Abstract: We studied risk-taking behaviour of breeding greylag geese Anser anser in western Poland. Our objectives were to test predictions resulting from the parental investment theory by observing variation in flushing distance for incubatingfemalesinrelationtoclutchsize,stageofincubation,nesttype and number of human visits to the nests. We found that the best predictor of flushing distance was the stage of breeding; a negative relationship was observed between the number of incubation days and the observed flushing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…Repeated visits to nests had no influence on the female flushing distance in our study, and similar results have been reported by Sjöberg () for Canada Geese and Osiejuk and Kucyński () for Greylag Geese. Previous authors have suggested that incubating geese might respond to repeated visits by humans in two different ways (Forbes et al.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Repeated visits to nests had no influence on the female flushing distance in our study, and similar results have been reported by Sjöberg () for Canada Geese and Osiejuk and Kucyński () for Greylag Geese. Previous authors have suggested that incubating geese might respond to repeated visits by humans in two different ways (Forbes et al.…”
Section: Discussionsupporting
confidence: 93%
“…In other species of geese, this negative relationship has been reported as either weak (Upland Geese, Chloephaga picta ; measuring egg density rather than nest age, Quillfeldt et al. ) or moderately significant (Greylag Geese, Anser anser ; Osiejuk and Kucyński ). In addition, a negative relationship between flushing distance and nest age was found to be significant for one of eight species of ducks and nearly significant for a second species (Forbes et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated how nest‐site characteristics affect risk‐taking behaviours (Albrecht & Klvaňa ; Osiejuk & Kuczyński ) and stress physiology (D'Alba et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Blumstein 2006; Møller 2010), we assessed escape behaviour by using an approaching human as a proxy for a predatory threat, and measured the distance at which the bird fled its nest. In nesting birds, escape distances are known to be related to degree of concealment through vegetation cover (Klvan et al 2004;Miller et al 2013), as well as stage of egg development (Osiejuk and Mickiewicz 2007), and colonial versus solitary breeding (Šálek and Cepáková 2006). However, to our knowledge the present study is the first to investigate escape behaviour in relation to directly quantified camouflage, as seen by the visual systems of relevant predators.…”
Section: Introductionmentioning
confidence: 99%